2020
DOI: 10.3390/ph14010002
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Essential Oil from Mentha piperita Ameliorates PM10-Exposed Asthma by Targeting IL-6/JAK2/STAT3 Pathway Based on a Network Pharmacological Analysis

Abstract: Fine particulate matter (PM) exposure exhibits a crucial risk factor to exacerbate airway epithelial remodeling, fibrosis, and pulmonary destruction in asthma. Based on the use of essential oils from aromatic plants on pain relief and anti-inflammatory properties, we investigated the inhibitory effects of essential oil derived from the Mentha species (MEO) against asthma exposed to PM10. The MEO (0.1 v/v %) was aerosolized by a nebulizer to ovalbumin and PM10-induced asthmatic mice. Histological changes were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It was shown that the splenocytes from S-(deg-S2) and S-(S2-1194) immunized mice secreted higher levels of T-helper-1 (TH1) cytokines (IFNγ, IL-2, and IL-12), whereas the splenocytes from WT and S-(deg-RBD) immunized mice secreted higher levels of T-helper-2 (TH2) cytokines (IL-4, IL-6, and IL-13) ( Fig. 4 ) ( 16 20 ). Overall, all RNA vaccines with deletion of glycosites elicited antibody and CD4 + and CD8 + T cell responses and related cytokines, with a stronger IFNγ-producing CD8 + T cell response in mice immunized with S-(deg-S2) and S-(S2-1194).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the splenocytes from S-(deg-S2) and S-(S2-1194) immunized mice secreted higher levels of T-helper-1 (TH1) cytokines (IFNγ, IL-2, and IL-12), whereas the splenocytes from WT and S-(deg-RBD) immunized mice secreted higher levels of T-helper-2 (TH2) cytokines (IL-4, IL-6, and IL-13) ( Fig. 4 ) ( 16 20 ). Overall, all RNA vaccines with deletion of glycosites elicited antibody and CD4 + and CD8 + T cell responses and related cytokines, with a stronger IFNγ-producing CD8 + T cell response in mice immunized with S-(deg-S2) and S-(S2-1194).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that menthol-containing herbal extracts protect the kidneys in chemotherapy- ( 48 ) and gentamicin-induced ( 49 ) nephrotoxicity. Others have shown that menthol inhibited pulmonary inflammation and epithelial remodeling when inhaled by asthmatic animals ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Murine models for allergic asthma models combined with exposure to particulate matter showed that PM 2.5 and PM 10 exacerbated the allergic airway response by further inducing a disbalance between the Th1 and the Th2 response with increased inflammatory cell infiltration, airway hyperreactivity, allergen-induced IgE, an increase in IL-4, IL-5 and IL-13 and decrease in IFN-γ and T-bet [121][122][123][124].…”
Section: Particulate Mattermentioning
confidence: 99%